Feeling Interpersonally Controlled While Pursuing Materialistic Goals: A Problematic Combination for Moral Behavior. (September 2018) - Sheldon, Kennon M.; Sommet, Nicolas; Corcoran, Mike; Elliot, Andrew J.
We created a life-goal assessment drawing from self-determination theory and achievement goal literature, examining its predictive power regarding immoral behavior and subjective well-being. Our source items assessed direction and energization of motivation, via the distinction between intrinsic and extrinsic aims and between intrinsic and extrinsic reasons for acting, respectively. Fused source items assessed four goal complexes representing a combination of direction and energization. Across three studies ( N s = 109, 121, and 398), the extrinsic aim/extrinsic reason complex was consistently associated with immoral and/or unethical behavior beyond four source and three other goal complex variables. This was consistent with the triangle model of responsibility's claim that immoral behaviors may result when individuals disengage the self from moral prescriptions. The extrinsic/extrinsic complex also predicted lower subjective well-being, albeit less consistently. Our goal complex approach sheds light on how self-determination theory's goal contents and organismic integration mini-theories interact, particularly with respect to unethical behavior.